A comprehensive literature review on friction stir welding: Process parameters, joint integrity, and mechanical properties - Kilic, Suleyman; Ozturk, Fahrettin; Demirdogen, Mehmet Fatih (Maǧallaẗ al-abḥath al-handasiyyaẗ, 2025)
Friction stir welding is not only a solid-state joining method used mostly for metals and alloys, but also, used for joining various polymer materials. This literature review includes information about the process parameters, joint integrity, and mechanical properties of FSW welded joints. Process parameters have a great influence on the quality of the weld joints. In particular, basic process variables such as tool design, rotational speed, welding speed, and axial force were reviewed in this study. By optimizing these process parameters, weld strength can be increased by minimizing welding defects. In addition, the effects of the FSW method on mechanical properties such as hardness, tensile, and fatigue behaviors were discussed. Finally, some suggestions were made for using the method. This literature review aims to be a resource for researchers and those interested in the FSW method to make decisions based on process optimization, design, and material selection.